Fenomen „Gazety Wyborczej” - Madera, Andrzej Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
Since the first issue of „GazetaWyborcza”was published, onMonday 8thMay 1989, it has become a true phenomenon on the Polish press market. After two months from the first publication it became very popular due to the slogan created by A. Michnik „your President – our Prime Minister”. „Gazeta Wyborcza” as the first newspaper published in democratic Poland became more than the biggest source of information as it also had a great influence on shaping of the political opinions of many Poles. It also supported the „Solidarity” movement and the new government. „Gazeta Wyborcza” was the first newspaper in democratic Poland whereone could find uncensored articles addressed to people, respecting their expectations and the right to information free from censorship. There is no doubt that „Gazeta Wyborcza” created by Adam Michnik, editor-in-chief, has currently got as many readers as critics but it is impossible to remain  unaffected  by  its  content.